Exploring the Influence of Rococo Style on Contemporary Fashion Clothing Styles - Li, Ruoxi (Transactions on Social Science, Education and Humanities Research, 2025)
This article explores the translation cases and innovative practices of Rococo style in different contemporary design fields. The Rococo style originated during the reign of Louis XV in early 18th-century France and is known for its delicate and intricate design language, as well as its pursuit of naturalism and hedonism in aesthetic expression. In contemporary times, through material innovation, structural reconstruction, functional decoration, cross-cultural dialogue, and other means, the Rococo style has been reborn in the fields of clothing design, home space, product design, and more. This article analyzes multiple typical cases, such as Gucci's AI-generated silk, Alexander McQueen's digital scanning and 3D printing technology, Boffi and Rolls-Royce's jointly developed kitchen system, etc., revealing the paradigm breakthrough of Rococo style in contemporary revival and the challenges and future directions it faces. Research has shown that the contemporary translation of Rococo style relies on three innovative mechanisms: symbol purification, technological intervention, and ethical reconstruction. However, there is also a risk of cultural misreading, and future design needs to further expand the boundaries of dynamic decoration and digital fashion.